2015
DOI: 10.1111/all.12758
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing Parkinson's disease among patients with asthma: a nationwide longitudinal study

Abstract: Patients with asthma had an elevated risk of developing Parkinson's disease later in life, and we observed a dose-dependent relationship between greater asthma severity and a higher risk of subsequent Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…24 A study using the Taiwan National Health Insurance Research Database found a positive, but not significant, association between PD and allergic rhinitis (hazard ratio = 1.29 [0.97–1.72]). 25 We found that PD was also associated with allergies to plants and antibiotics, but not with allergies to food or animals (Supplementary Data 1). Understanding the biological differences between these different groups of allergies may allow us to hone in on specific immunological pathways that contribute to PD risk.…”
Section: Discussionmentioning
confidence: 84%
“…24 A study using the Taiwan National Health Insurance Research Database found a positive, but not significant, association between PD and allergic rhinitis (hazard ratio = 1.29 [0.97–1.72]). 25 We found that PD was also associated with allergies to plants and antibiotics, but not with allergies to food or animals (Supplementary Data 1). Understanding the biological differences between these different groups of allergies may allow us to hone in on specific immunological pathways that contribute to PD risk.…”
Section: Discussionmentioning
confidence: 84%
“…This study uncovered that the β2AR agonist salbutamol, a drug commonly prescribed to treat asthma, was associated with a reduced risk of developing PD in a Norwegian population. Although a connection between allergic diseases and PD is rare, a cross-sectional retrospective study revealed that patients with asthma had an increased risk of PD in a Taiwanese population (Cheng et al, 2015 ). The relationship between asthma and PD remains unknown.…”
Section: Personalized Medicine In Parkinson’s Diseasementioning
confidence: 99%
“…To ensure diagnostic validity and patient homogeneity, we collected only patients diagnosed by otolaryngologists and neurologists, with at least two consistent tinnitus diagnoses to improve diagnostic validity. Similar methods for the identification of AD and PD had been applied in previous studies 24,25 . In Taiwan, PD is usually diagnosed by neurologists and two of the four main symptoms (shaking or tremor; slowness of movement, called bradykinesia; stiffness or rigidity of the arms, legs or trunk; trouble with balance and possible falls, also called postural instability) must be present over a period of time to consider a PD diagnosis.…”
Section: Study Populationmentioning
confidence: 99%